An efficient peer to peer energy trading system through multichain private block chain using PV generation. - Hassan, Yamin; Mazumder, Sagar; Rahman, Ashfakur; Hossain, Ashik (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.